The application of two drainage angles in neurocritical care patients with complicated pneumonia: a randomized controlled trial - Anna Zhao; Huangrong Zeng; Hui Yin; Jinlin Wang; Wenming Yuan; Chao Li; Yan Zhong; Lanlan Ma; Chongmao Liao; Hong Zeng; Yan Li (PeerJ, 2024)
Background Although head elevation is an early first-line treatment for elevated intracranial pressure (ICP), the use of the head-down or prone position in managing neurocritical patients is controversial because a change in a position directly affects the intracranial and cerebral perfusion pressure, which may cause secondary brain injury and affect patient outcomes. This study compared the effects of two postural drainage positions (30° head-up tilt and 0° head flat) on the prognosis of neurocritical care patients with complicated pneumonia and a clinical pulmonary infection score (CPIS) ≥5 points to provide a reference for selecting appropriate postural drainage positions for patients with pneumonia in neurocritical care units. Methods A prospective randomized controlled study was conducted with 62 neurocritical care patients with complicated pneumonia. The patients were categorized into control (=31) and experimental (=31) groups in a 1:1 ratio using a simple randomized non-homologous pairing method. Emphasis was placed on matching the baseline characteristics of the two groups, including patient age, sex, height, weight, Glasgow Coma Scale score, heart rate, mean arterial pressure, cough reflex, and mechanical ventilation usage to ensure comparability. Both groups received bundled care for artificial airway management. The control group maintained a standard postural drainage position of 0° head-flat, whereas the experimental group maintained a 30° head-up tilt. The efficacy of the nursing intervention was evaluated by comparing the CPIS and other therapeutic indicators between the two groups after postural drainage. Results After the intervention, the within-group comparison showed a significant decrease in the CPIS (P < 0.001); procalcitonin levels showed a significant decreasing trend (P < 0.05); the arterial oxygen pressure significantly increased (P < 0.05); the oxygenation index significantly increased (P < 0.001); and the aspiration risk score showed a significant decreasing trend (P < 0.001). A between-group comparison showed no significant differences in any of the indicators before and after the intervention (P < 0.05). Conclusion Postural drainage positions of 30° head-up tilt and 0° head-flat can improve the CPIS and oxygenation in patients without adverse effects. Therefore, we recommend that patients under neurological intensive care and having pneumonia be drained in a 30° head-up tilt position with good centralized care of the lung infection. Trial registration The study, “Study of Angles of Postural Drainage in Neurocritical Patients with Pneumonia,” was registered in the Protocol Registration Data Element Definitions for Interventional Study database (# ChiCTR2100042155); date of registration: 2021-01-14.